1997
DOI: 10.1111/j.1945-5100.1997.tb01299.x
|View full text |Cite
|
Sign up to set email alerts
|

Suevite breccia of the Ries impact crater, Germany: Petrography, chemistry and shock metamorphism of crystalline rock clasts

Abstract: Abstract— Clasts of deep‐seated crystalline basement rocks in suevites of the Ries crater, Germany, were catalogued lithologically and classified with regard to their degree of shock metamorphism. The sample suite consisted of 806 clasts from 10 outcrops in fallout suevites and 447 clasts from drill cores encountering crater suevite in the crater interior. These clasts can be grouped into seven types of metamorphic and nine types of igneous rocks. One hundred forty‐three clasts, representing these lithologies,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
176
0
3

Year Published

2002
2002
2020
2020

Publication Types

Select...
2
2
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 89 publications
(185 citation statements)
references
References 14 publications
6
176
0
3
Order By: Relevance
“…Within the pipes, the fine-grained matrix of the suevite has been removed, leaving the filling of coarser fragments that are coated with a light brown layer of undetermined Fe-rich oxide material (Newsom et al 1986). Engelhardt (1997) concluded that there is no coherent impact melt sheet at the Ries crater. Moreover, Stöffler (1977) suggested if there exists such a sheet or lens, deep-seated in the crater centre, it would be of minor size.…”
Section: Geological Settingmentioning
confidence: 99%
See 4 more Smart Citations
“…Within the pipes, the fine-grained matrix of the suevite has been removed, leaving the filling of coarser fragments that are coated with a light brown layer of undetermined Fe-rich oxide material (Newsom et al 1986). Engelhardt (1997) concluded that there is no coherent impact melt sheet at the Ries crater. Moreover, Stöffler (1977) suggested if there exists such a sheet or lens, deep-seated in the crater centre, it would be of minor size.…”
Section: Geological Settingmentioning
confidence: 99%
“…The crater-fill suevites form a massive (up to 400 m thick) layer in the crater depression below the post-impact crater lake sediments (Engelhardt et al 1995). The crater suevite is a polymict breccia with lesser amount of glassy material as compared to surficial suevites (Engelhardt et al 1995;Engelhardt 1997).…”
Section: Geological Settingmentioning
confidence: 99%
See 3 more Smart Citations